2019
DOI: 10.3991/ijet.v14i20.11463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobile Augmented Reality (MAR) towards Students’ Visualization Skills when Learning Orthographic Projection

Abstract: Recent study shows an increasing interest towards the implementation of augmented reality in teaching and learning. Majority of the studies in this area focuses on how this technology could impact students’ performance and various skills including visualization skills. Hence, the purpose of this study was to examine the differences in students’ visualization skills after utilizing Mobile Augmented Reality (MAR) and conventional learning in orthographic projection classroom. This study involved 60 students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…Improved mental modelling is supported by studies by Omar et al . () and Nuanmeesri (), both of which found that the use of AR enabled more effective visualisation; to confirm whether this is the case here, a stage of articulation and reflection could be used following the completion of the operations.…”
Section: Discussionsupporting
confidence: 54%
“…Improved mental modelling is supported by studies by Omar et al . () and Nuanmeesri (), both of which found that the use of AR enabled more effective visualisation; to confirm whether this is the case here, a stage of articulation and reflection could be used following the completion of the operations.…”
Section: Discussionsupporting
confidence: 54%
“…Due to its importance in many areas, the support of mental rotation constitutes an important area of research. Meanwhile, there is ample evidence that MRA can be improved by training [10], [40]- [42] and that the effects of training can be transferred to other tasks [43]. According to some authors, cognitive processes underlying mental rotation are linked to actual physical rotation and can activate corresponding motor processes.…”
Section: Mental Rotation Abilitymentioning
confidence: 99%
“…[7] Tujuan dari proyeksi paralel adalah untuk menggambarkan objek sesuai dengan proporsi nya sehingga mempermudah pengamatan dan membayangkan proporsi ukuran. [8] Gambar 1. Koordinat 3D Jika Xp dan Yp adalah koordinat pada proyeksi seperti yang diperagakan pada Gambar 2.…”
Section: A Proyeksi 3d Paralel Dengan Kaidah Tangan Kananunclassified